Impact of Communication Apprehension and Communication Skills Training on Interaction in a Distance Education Course - Kathleen Dodge Kelsey (Journal of Applied Communications, 2000)
The importance of providing students with skills necessary for success in distance education classrooms is uncontested; however, few universities have done so. This case study sought to answer two questions: (a) What was the impact of communication apprehension (CA) on distance education students who experience the trait; and (b) What was the impact of a skills training session on interaction in a distance education course? Findings indicate that communication apprehensive students could not be motivated to interact regardless of interventions; however, non-CA students did benefit from the skills training session. An outline for a recommended skills training session based on recommendations from the literature and this study is included along with implications for educational practice.